Diverse roles for glycosaminoglycans in neural patterning. Issue 1 (30th August 2017) - Saied‐Santiago, Kristian; Bülow, Hannes E.
Abstract : The nervous system coordinates the functions of most multicellular organisms and their response to the surrounding environment. Its development involves concerted cellular interactions, including migration, axon guidance, and synapse formation. These processes depend on the molecular constituents and structure of the extracellular matrices (ECM). An essential component of ECMs are proteoglycans, i.e., proteins containing unbranched glycan chains known as glycosaminoglycans (GAGs). A defining characteristic of GAGs is their enormous molecular diversity, created by extensive modifications of the glycans during their biosynthesis. GAGs are widely expressed, and their loss can lead to catastrophic neuronal defects. Despite their importance, we are just beginning to understand the function and mechanisms of GAGs in neuronal development. In this review, we discuss recent evidence suggesting GAGs have specific roles in neuronal patterning and synaptogenesis. We examine the function played by the complex modifications present on GAG glycans and their roles in regulating different aspects of neuronal patterning. Moreover, the review considers the function of proteoglycan core proteins in these processes, stressing their likely role as co‐receptors of different signaling pathways in a redundant and context‐dependent manner. We conclude by discussing challenges and future directions toward a better understanding of these fascinating molecules during neuronal development. Developmental Dynamics 247:54–74, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Glycosaminoglycans serve specific and instructive roles in neural patterning. Glycosaminoglycans serve specific roles in synaptic development and function. The molecular diversity (a glycosaminoglycan code) contributes to the functional specificity. Glycosaminoglycans serve redundantly to regulate cell‐cell signaling during development of the nervous system. The function of glycosaminoglycans in regulating signaling pathways is conserved throughout evolution.